2019
DOI: 10.1177/0192623319875085
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Regulatory Policy Committee Points to Consider*: Approaches to the Conduct and Interpretation of Vaccine Safety Studies for Clinical and Anatomic Pathologists

Abstract: The design and execution of toxicology studies supporting vaccine development have some unique considerations relative to those supporting traditional small molecules and biologics. A working group of the Society of Toxicologic Pathology Scientific and Regulatory Policy Committee conducted a review of the scientific, technical, and regulatory considerations for veterinary pathologists and toxicologists related to the design and evaluation of regulatory toxicology studies supporting vaccine clinical trials. Muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 79 publications
2
18
0
Order By: Relevance
“…Additional studies acquire knowledge on timing of administrations, total number of doses, and induction (priming) and booster (maintenance) intervals to establish a rationale for an initial clinical schedule. 84,102 A lack of widely accepted allometric scaling approaches to calculate an equivalent dose across species limits translatability, providing only a rough estimate to support clinical trial designs. [103][104][105] The optimal dose in a personalized TCV will likely vary across antigens, and the total antigen dose must ensure delivery of adequate amounts of the less immunogenic antigens.…”
Section: Vaccination Strategy: Dosing and Administrationmentioning
confidence: 99%
“…Additional studies acquire knowledge on timing of administrations, total number of doses, and induction (priming) and booster (maintenance) intervals to establish a rationale for an initial clinical schedule. 84,102 A lack of widely accepted allometric scaling approaches to calculate an equivalent dose across species limits translatability, providing only a rough estimate to support clinical trial designs. [103][104][105] The optimal dose in a personalized TCV will likely vary across antigens, and the total antigen dose must ensure delivery of adequate amounts of the less immunogenic antigens.…”
Section: Vaccination Strategy: Dosing and Administrationmentioning
confidence: 99%
“…With reference to the injection site, the quadriceps muscle from both sides and from all animals were divided into 3 portions (i.e., cranial, central, distal) and embedded in paraffin. This trimming procedure followed the recommendation of Sellers et al, 18 in order to achieve optimal sampling of the site of injection. From the overlying skin, a single sample was processed, corresponding to the central portion of the skin injection site.…”
Section: Observations and Examinationsmentioning
confidence: 99%
“…[12][13][14][15] Since the SARS-CoV-2 vaccines are developed as preventive measures to be administered to a healthy population, it is of utmost importance to properly evaluate the safety of such vaccines in well-designed and GLP-compliant preclinical toxicity studies. [16][17][18] Therefore, the aim of this study was to assess the systemic toxicity and local tolerance of the TKSB01 plasmid in Sprague Dawley (SD) rats, delivered intramuscularly and followed by EP.…”
Section: Introductionmentioning
confidence: 99%
“…The typical nonclinical toxicity study design, commonly observed findings and risk assessment strategies were discussed in detail in a recently published STP SRPC Points to consider paper on vaccine safety studies. 40 This current review is written with the expectation that it will be read in context with the previously published SRPC manuscript. Since most SARS-CoV-2 vaccine candidates are expected to use platform technologies with previously generated nonclinical and clinical safety data, this review only addresses potential theoretical safety risks associated with SARS-CoV-2 vaccine candidates.…”
Section: How To Address the Potential Theoretical Safety Risks Associmentioning
confidence: 99%
“…Regulatory toxicology studies for vaccines generally follow similar study design as small molecule and biotherapeutics, with additional end points to assess acute phase response and immunogenicity of the vaccine antigens. Regulatory guidelines and key aspects of regulatory toxicology studies (study design, study conduct, commonly observed findings, and interpretation) for vaccines were reviewed in a recently published Society of Toxicologic Pathology (STP) Scientific and Regulatory Policy Committee (SRPC) Points to Consider article in Toxicologic Pathology 40 and covered in an STP Continuing Education course in August 2020.…”
Section: How Can the Development Of Coronavirus Vaccines Be Accelerated?mentioning
confidence: 99%